(untitled) (Journal of the College of Basic Education, 2022)
The approach of the books of the meanings of the Qur’an is based on the logical reasoning in the analysis and interpretation of the aspects of syntax. The books of meanings turn the matter over on its various aspects, and explain each aspect of it to reach the result that you satisfy. The multiplicity of syntactic possibilities is considered one of the phenomena that distinguish grammatical thinking. There is no doubt that this phenomenon showed the ability of the owners of the books of meanings to fulfill all possible faces and to penetrate them into what is implied by the texts of the saying and the methods of speech in order to reach the correctness of the syntax.